Tingkat Pemahaman Mahasiswa Terhadap Pendidikan Karakter Di Jawa Timur Pada Era New Normal - Khan Khayru, Rafadi; Sudja’i, Sudja’i (Jurnal Simki Pedagogia, 2022)
The education system that adapts to the post-Covid-19 era is marked by the "new normal" era. On the other hand, the transition of character education in the family environment brings a new problem, namely the lack of concept of character education in the family environment. Finally, there is the urgency of academic moral degradation in the millennial generation. Therefore, education is required to transform to provide strengthening character education in Indonesia. This study was conducted to determine students' understanding of character education and how students provide solutions to the threat of moral decline in the new normal era. This type of research is qualitative research. The sample selection used the accidental sampling method. With a sample of 24 from students in East Java. The data from this study were obtained from filling out questionnaires using Google Forms and distributing information through posters on Instagram. In this study, it was found that students already understood the importance of character education and could provide ways or solutions to shape character in the new normal era.